NILAI KEARIFAN LOKAL RUMAH TRADISIONAL JAWA - Djono Djono; Tri Prasetyo Utomo; Slamet Subiyantoro (Humaniora, 2012)
Java has the values that can be taken in relation to the value of the benefits of ethics and aesthetics. One farm of those values are joglo art that have the local knowledge of Javanese culture. Model approach in this research is leading to a descriptive qualitative ethnographic, in which the empirical reality a result, demanding researchers go directly to the location of the study, to be able to live up to their tradition, and the symptoms of everyday life that is full of social phenomena local culture. This research firms a single case study stuck. In the context of this case study, a traditional Javanese home visits as a sub unit of analysis, but its existence still viewed/reviewed as a place that is part of the social system of the larger society around Surakarta. Java house building structure is one that reflects the composition of space like typical building pendhapa, pringgitan, dalem, kitchen, or gadri gandhok. The relation between this structure is a structure which is strongly influenced by the manifestation process mythology and cosmology Java). This means that the traditional Javanese house is not just a place to shelter (practical function), but also understood as a manifestation of the ideals and outlook on life or a symbolic function. In this case the traditional Javanese houses are not only placed as an autonomous element, a separate stand alone, but being seen in context, particularly relevant to the context of allied Javanese cosmology that underlie the view that the Javanese philosophy of Iife.